ТНЕ INVESTIGATION OF PERFORMANCE CHARACTERISTICS OF SAPONITE GRANULATE - GANZYUK, ALLA; MASLO, LESYA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The use of natural clays in production and environmental protecting measures is provided by their mineral compounds, physical and chemical properties which are defined by the composition and size of clay part. In terms of ecology that is expedient, as the clay minerals almost don’t have compounds that pollute waters and they are natural for such areas. It has been investigated the problems of the Ukrainian market of petroleum products and suggested the ways to solve them by developing of a program for the transition to Euro environmental standards and alignment of Ukrainian standards with the European ones. The influence of the granulation process on the sorption properties of the obtained granulated aluminosilicates has been investigated. The main operational characteristics of the received saponite granulate namely: the stability and strength of the granules in gasoline over a given period of time; it has been evaluated the water resistance and oil capacity of sorption materials based on layered aluminosilicates. It has been shown that the activation of natural sorption materials with acids does not significantly affect the indicators of heat resistance and destruction processes in the saponite-activator system. Moreover, granulation improves the strength and filtration characteristics of natural sorbents by increasing the filtration rate. The results of the research allow us to recommend the obtained sorbent materials as an efficient filtering charge for cleaning and controlling specific properties as a filter load for cleaning hydrocarbon mixtures and for obtaining high-quality, high-octane and low-toxic fuels. It was established that the obtained sorption material based on saponite clay improves the basic exploitative characteristics of the fuel. Its application allow to solve the problem of reducing toxic emissions of e.g. motor vehicles in atmosphere.
Keywords: adsorption; petroleum products; chromatography; octane rating; saponite; vapor pressure